Improvement of look ahead based on quadratic approximation for crystal structure prediction. Issue 1 (31st December 2022) - Yamashita, Tomoki; Sekine, Hirotaka
ABSTRACT: Crystal structure prediction based on first-principles calculations is usually time-consuming since a lot of candidate structures have to be locally optimized. Look Ahead based on Quadratic Approximation, which is one of the selection-type algorithms we previously developed, can control the optimization priority of the candidates. It can efficiently reduce the computational costs in many cases, however, it has been found to be inefficient in some data sets. In the present study, we proposed an improved score of Look Ahead based on Quadratic Approximation, where the stress term is added to overcome the drawbacks of the previous score. Crystal structure prediction simulations by this improved algorithm are performed to investigate the searching efficiency for typical materials such as Si, Al2 O3, NaCl, and SrCO3 . These results demonstrate that this improved algorithm reduces the searching cost to less than 40% with respect to random search in most cases. The introduction of the stress term makes this algorithm more robust and versatile. GRAPHICAL ABSTRACT: uf0001